Pengaruh Gaji dan Motivasi Kerja terhadap Produktivitas Guru SMA Della Strada - Dhana, Agnes; Iskandar, Donant Alananto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
The aim of this research is to determine the effect of salary and work motivation on teacher productivity.The conceptual model is a summary of a thought, the relationship between the variables. In this research, the researcher used variables namely, the effect of salary, work motivation, and productivity. With the object of research, namely SMA Della Strada teacher. This study uses a quantitative method with saturated sampling technique. Data collection is done by distributing questionnaires via google form to 30 respondents who will be processed using SPSS 25.Based on the results of the research, the following conclusions can be drawn as follows: There is a significant positive effect of salary on teacher productivity at Della Strada High School which means that the more appropriate the salary given, the productivity will increase and vice versa. There is a significant positive effect of motivation on teacher productivity at Della Strada High School which means that the more appropriate the motivation given, the productivity will increase and vice versa. There is a significant effect of motivation on teacher productivity at SMA Della Strada. Salary and motivation variables can affect productivity by 61.2%.